Prevalencia del corona virus canino y su variación con alteraciones hematológicas en perros, atendidos en la clínica veterinaria caninos y felinos - Yumbla Paredes, Jocelyne Lisbeth (2024)
Canine coronavirus (CCV) is a viral disease that primarily affects the gastrointestinal system of dogs, causing symptoms such as diarrhea, vomiting, lethargy, and loss of appetite. Due to its high transmissibility and the impact, it has on the animals' general health, this research aimed to determine the prevalence of CCV in patients treated at the Canine and Feline Veterinary Clinic and analyze its possible association with hematological disorders. The problem arises from the limited local information on this disease and its effects on the blood system, which hinders early diagnosis and limits adequate therapeutic options. This situation highlights the need for scientific studies to strengthen veterinary knowledge in the region. A cross-sectional and descriptive study was conducted, which included 110 dogs with clinical signs suggestive of CCV infection. All patients underwent rapid immunochromatographic tests to confirm the presence of the virus, and complete blood counts were performed to identify possible alterations in parameters such as hematocrit, hemoglobin, red blood cells, white blood cells, lymphocytes, eosinophils, and platelets. The problem arises from the limited local information available regarding this viral disease and its impact on the blood system, which hinders early diagnosis and limits therapeutic options. This situation highlights the need for research that contributes to optimizing veterinary care. To this end, a cross sectional, descriptive study was conducted, including dogs with clinical signs suggestive of CCV infection. Rapid tests were applied to confirm the presence of the virus, and hematological analyses were performed to identify possible abnormalities in the positive dogs. One hundred and ten dogs were evaluated, of which 20 tested positive, representing 18.18% of the total sample. Of these, 12 presented significant hematological abnormalities, while the remaining 8 showed no significant changes in their blood parameters. In conclusion, the results obtained underscore the importance of canine coronavirus as a common problem in veterinary clinics. Therefore, it is important for animals to be vaccinated, dewormed, and receive a quality diet that allows them to maintain a strong immune system against infections.